SUPERVISI MANAJEMEN PENDIDIKAN DI PONDOK AL-MUSLIMUN MENUJU GENERASI UNGGUL DI ERA GLOBALISASI - Efriani, Efriani; Yusrianti, Susi (Center for Research and Community Service (LPPM) University of Abulyatama, 2024)
In the contemporary era of globalization, the supervision of education plays a pivotal role in shaping competent individuals capable of navigating the complexities of modern life while upholding Islamic principles. This study delves into the essence of educational supervision within the framework of an integrated Islamic educational institution, aiming to prepare a generation of scholars adept in both worldly affairs and spiritual pursuits. By elucidating the core objectives and methodologies outlined by Dayah Terpadu Al-Muslimun, this research investigates how a comprehensive curriculum, blending modern and Salafi pedagogies, nurtures graduates who embody holistic Islamic values. The study reveals that through a curriculum rooted in Islamic principles and supplemented by the national religious curriculum, students develop a strong foundation in faith, knowledge, and ethics, alongside proficiency in Arabic, English, technology, and organizational skills. The findings underscore the significance of a balanced education that harmonizes religious teachings with contemporary knowledge, fostering individuals who are not only intellectually astute but also morally upright. In conclusion, this research advocates for educational supervision strategies that prioritize the cultivation of well-rounded individuals capable of contributing positively to both the Muslim community and global society